2012
DOI: 10.1002/hyp.9501
|View full text |Cite
|
Sign up to set email alerts
|

Surface water–groundwater interaction at restored streams and associated reference reaches

Abstract: Stream restoration goals include improving habitat and water quality through reconstruction of morphological features found at analogous, pristine stream reaches. Enhancing hyporheic exchange may facilitate achieving these goals. Although hyporheic exchange at restoration sites has been explored in a few previous studies, comparative studies of restored versus reference or control streams are largely absent. We hypothesized that restoration cross-vanes enhance hyporheic exchange, resulting in biogeochemical al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 67 publications
3
41
1
Order By: Relevance
“…Our results suggest that restoration shifted the groundwater discharge zone and increased its spatial extent. One explanation for the difference in findings is that Daniluk et al (2013) studied sites 6 to 8 y after restoration, whereas we studied a newly restored site. Clogging of the top layer of channel sediments can occur over time following restoration, thereby reducing hydraulic conductivity of bed sediments and shifting patterns of surfacewater-groundwater interaction through time (Kasahara and Hill 2006).…”
Section: Zones Of Upwelling and Downwelling Pre-and Postrestorationmentioning
confidence: 58%
See 4 more Smart Citations
“…Our results suggest that restoration shifted the groundwater discharge zone and increased its spatial extent. One explanation for the difference in findings is that Daniluk et al (2013) studied sites 6 to 8 y after restoration, whereas we studied a newly restored site. Clogging of the top layer of channel sediments can occur over time following restoration, thereby reducing hydraulic conductivity of bed sediments and shifting patterns of surfacewater-groundwater interaction through time (Kasahara and Hill 2006).…”
Section: Zones Of Upwelling and Downwelling Pre-and Postrestorationmentioning
confidence: 58%
“…A distinct layer of higher permeability materials overlaying lower permeability materials could produce an effective anisotropy that favors flow parallel to the layers and hinders flow and mixing perpendicular to the layers (Marion et al 2008, Sawyer and Cardenas 2009, Marklund and Wörman 2011. Daniluk et al (2013) observed stronger influence of groundwater upwelling on porewater geochemistry in reference reaches than in restored reaches, and concluded that restoration did not enhance the groundwater connection to the stream bed. Our results suggest that restoration shifted the groundwater discharge zone and increased its spatial extent.…”
Section: Zones Of Upwelling and Downwelling Pre-and Postrestorationmentioning
confidence: 89%
See 3 more Smart Citations